Pemberdayaan Masyarakat Tani Nelayan dan Peternak (Studi pada Dinas Tanaman Pangan Hortikulturan dan Perkebunan Provinsi Papua Barat) - Indiati Indiati; Muhamad Pattiran; Sigit Wahyudi (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
Special Efforts for the Protection and Empowerment of Farmers, Fishermen and Breeders to build local communities to improve welfare and a better standard of living, so that all people participate in all areas of life. The purpose of this paper is to find out how the form of protection and empowerment of Fishermen and Livestock Farmers in West Papua Province. The research method used is qualitative research method, the type of research used is literature research, observation and random approach to farmer groups, fishermen, and breeders in the field. The results of this study indicate that the role of the government in implementing protection and empowerment of farmers, fishermen and breeders as Regulators, Facilitators, and Catalysts. Concretely, the form of protection and empowerment of farmers, fishermen and breeders can be done by forming farmer groups to facilitate the distribution of information through agricultural counseling and training in general to groups of farmers, fishermen and breeders. Forms of protection - Farmer Protection and Empowerment is based on a. sovereignty; b. independence; c. usefulness; d. togetherness; e. integration; f. openness; g. efficiency-justice; and h. sustainability. The protection and empowerment of farmers, fishermen and livestock is the responsibility and obligation of the government must be carried out in a just, trustful, and non-discriminatory manner as a prerequisite for realizing welfare